Solo instrumental concert with the participation of folk and percussion instruments in the context of the new european tradition - Shapovalova, Liudmyla; Kysliak, Bohdan; Vavryk, Ruslana; Zinchenko, Viktoriia; Katryniak, Bohdan (MAGNANIMITAS Academic Association, 2024)
The article makes an attempt to comprehend the evolution and development of instrumental concert with solo on folk and percussion instruments. New European musical culture is considered from the standpoint of not only musical theory, but also synergy and philosophy. Special attention in the study is given to bayan and accordion.
Keywords: Музична культура європейська, концерти інструментальні соло, перформанс музичний, перформанс інструментальний